Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Kecerdasan Spiritual Siswa SMK - Irawati; Khusni Albar, Mawi (Jurnal Pendidikan Agama Islam, 2025)
In this modern era, the younger generation is facing an increasingly concerning moral crisis. The role of Islamic religious education teachers is crucial in instilling religious values ​​through the application of effective and appropriate learning strategies. This study aims to determine the strategies implemented by Islamic Religious Education (PAI) teachers in an effort to improve students' spiritual intelligence at SMK Negeri 1 Kaligondang. In facing moral challenges and character crises in the modern era, spiritual intelligence is an important aspect that must be instilled early on through an educational approach. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Meanwhile, the data analysis technique uses qualitative data analysis interactive models from Miles and Huberman which include data reduction, data presentation and drawing conclusions. In addition, to test the validity of the data, triangulation techniques were used. The results of the study showed that PAI teachers implemented various strategies, including the habituation of daily religious activities such as congregational dhuha and dzuhur prayers, memorizing short letters, as well as using Islamic storytelling methods, exemplary methods and talaqqi methods in the learning process. These strategies have proven to be able to encourage students to better understand and practice religious values ​​in their daily lives. In addition, teacher role models and school environmental support are important factors in the process of improving students' spiritual intelligence.